The amount of ionizable fluoride in toothpastes available in Metro Manila - Abeleda, Katherine Lauren G.
Fluoride toothpastes had been established as a leading caries preventive measure. It has been known that the amount of ionizable fluoride and not total fluoride are the key to the effectiveness of fluoride toothpastes. Ionizable fluoride is part of the total fluoride that is free from other components of the toothpastes that act on dental hard tissues and prevent dental caries. The Federation Dentaire Internationale (FDI) recommended an amount of 1,000 to 1,450 ppm of ionizable fluoride in toothpastes. Proper labeling of toothpastes is important to inform the public on the contents and manufacturing details of the product they are purchasing. The directions of use of toothpastes in the packaging serve as a way of educating the public on its utilization. This study aimed to determine the amount of ionizable fluoride in fluoride toothpaste and the compliance to labeling requirements. The information obtained could help pave the way to the standardization of the amount of ionizable fluoride and proper labeling of toothpastes. Eight samples with different brand names were obtained through purposive sampling. The samples were then subjected to total, soluble and ionic fluoride testing using an Orion ion specific electrode. Deficiencies were found concerning the total and ionizable fluoride concentration of the toothpastes. One (1) sample complied to the Association of Southeast Asian Nations Harmonization Cosmetic Scheme on labeling. None of the samples fully satisfied the World Health Organization labeling recommendations.